Virtual Laboratory and Self-Efficacy in Optimizing Problem-Solving Skills: A Case in Applied Chemistry Learning in Vocational College - Ida Ayu Anom, Arsani; Ida Bagus Putra Manuaba; I Ketut, Darma; M, Yusuf (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The limitation of laboratory facilities in conducting practical chemistry learning activities has become one of the triggers for less optimal learning processes. Implementation of virtual laboratory simulation becomes a solution to overcome the limited equipment of practicum activities. It is possible to overcome some of the challenges that are currently being experienced in chemistry education by making effective use of virtual laboratories. The primary aim of this research is to investigate the impact of virtual laboratories and self-efficacy on the improvement of problem-solving skills among engineering students in the context of applied chemistry education. The research employs a quasi-experimental design to examine the impact of independent variables on dependent variables. Participants in this study are students enrolled in the Refrigeration and Air Conditioning Engineering and Utility Engineering Technology programs within the Mechanical Engineering Department of Bali State Polytechnic. The study utilized data collection instruments consisting of tests assessing problem-solving skills and questionnaires measuring self-efficacy. The current study employs analysis of covariance (ANCOVA) as a statistical method to examine the hypothesis.The hypothesis testing results show that using virtual laboratories has a better effect than problem-solving skill demonstrations when it comes to electroplating learning activities. The observed correlation between self-efficacy and improved problem-solving skills does not seem to result in a significant impact.